Live Duplicate Abuse on Shopee: Economic Impact Analysis and Sharia-Based Solutions - Meirina Tri Ananda Putri; Fahrurrozi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the phenomenon of live duplicate abuse on the Shopee platform and analyzes its economic impact through the lens of Islamic economics. Using a qualitative approach with content analysis and online interviews involving Shopee affiliates and customer service representatives, this research explores the ethical and economic implications of the misuse of live streaming features. The findings reveal that the practice of duplicating live broadcasts across multiple accounts not only violates Shopee’s policies but also creates unfair competition, decreases affiliate engagement, and reduces consumer trust in the platform. From an Islamic economic perspective, such actions contradict the principles of sidq (honesty), amanah (trustworthiness), and adl (justice), which are essential for maintaining fairness and transparency in digital transactions. The study suggests that implementing maqasid al-shariah values and reinforcing regulatory control over live commerce can prevent unethical practices, protect market integrity, and promote a more sustainable e-commerce ecosystem.